Analysis of the Role of Risk Based Audit in Banking - Tuti Dharmawati; Wa Ode Muhardiana; Ayu Puspita Rini; Ulvy Restiana Parintak; Sri Ardita Vitara Sartono Farihu (PT. Banjarese Pacific Indonesia, 2024)
Risk based audit (RBA) is an approach that is increasingly being applied in the banking sector to increase the effectiveness of risk management and compliance with regulations. This approach helps banks identify high-risk areas and prioritize audits according to the level of risk. This research uses qualitative methods with a literature research approach. Data sources consist of scientific journal articles, books, reports and documents related to risk-based and banking audits. Research findings show that the RBA has several key roles in improving banking performance. First, RBA improves operational efficiency and effectiveness by focusing audits on high-risk areas. Second, the RBA enables banks to proactively identify and manage risks, thereby strengthening financial and operational stability. Third, the RBA ensures that banks are more compliant with regulations and industry standards, reducing the risk of sanctions and fines. In addition, the implementation of RBA encourages the formation of a strong risk management culture and the use of information technology to support the risk management process. Risk based audit plays a significant role in improving banking performance. By improving operational efficiency, managing risk proactively, ensuring regulatory compliance, establishing a strong risk management culture, and leveraging technology, banks can achieve stability and better performance in the long term. These findings support the importance of implementing RBA as the main strategy in risk management and supervision in the banking sector.